2015
DOI: 10.1111/bjh.13868
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of T‐cell depletion in haploidentical stem‐cell transplantation

Abstract: T-cell depletion (TCD) can prevent the onset of graft-versus-host disease (GvHD) in animal models of bone marrow transplantation; this manipulation enabled the successful application in the 1980s of T-cell depleted bone marrow (BM) for the treatment of babies with severe combined immune deficiency (SCID). However, in leukaemia patients, implementation of T-cell depletion has been more difficult, especially due to high rate of graft-rejection, leukaemia relapse and delayed immune reconstitution. These hurdles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 96 publications
0
42
0
Order By: Relevance
“…T‐cell depletion (TCD) is important for haploidentical donor (haplo) hematopoietic cell transplantation (HCT) to reduce graft‐versus‐host disease (GVHD). TCD can be ex vivo in which T cells are removed from the allografts before infusion, or in vivo where anti‐lymphocyte antibodies or immunosuppressive drugs such as high‐dose cyclophosphamide are given to kill donor T cells after infusion . One early successful technique for haplo‐HCT gave an anti‐thymocyte globulin (ATG)‐containing preparative regimen with immunomagnetic enrichment of CD34+ cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T‐cell depletion (TCD) is important for haploidentical donor (haplo) hematopoietic cell transplantation (HCT) to reduce graft‐versus‐host disease (GVHD). TCD can be ex vivo in which T cells are removed from the allografts before infusion, or in vivo where anti‐lymphocyte antibodies or immunosuppressive drugs such as high‐dose cyclophosphamide are given to kill donor T cells after infusion . One early successful technique for haplo‐HCT gave an anti‐thymocyte globulin (ATG)‐containing preparative regimen with immunomagnetic enrichment of CD34+ cells .…”
Section: Introductionmentioning
confidence: 99%
“…TCD can be ex vivo in which T cells are removed from the allografts before infusion, or in vivo where anti-lymphocyte antibodies or immunosuppressive drugs such as high-dose cyclophosphamide are given to kill donor T cells after infusion. 1,2 One early successful technique for haplo-HCT gave an anti-thymocyte globulin (ATG)-containing preparative regimen with immunomagnetic enrichment of CD34+ cells. 3 This indirectly depleted T cells and other donor immune cells extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the clinical use of haploidentical donors has gained great momentum, either through the use of megadose T-cell-depleted (TCD) peripheral blood progenitor cells (PBPCs) or unmanipulated transplants followed by high-dose posttransplant cyclophosphamide (PTCY). 1,2 The former approach is more time consuming and requires costly graft processing but offers better prevention of graft-versus-host disease (GVHD). Notably, although some risk of GVHD is tolerable in the treatment of patients with hematologic malignancies, this is unacceptable in the case of haploidentical transplantation for nonmalignant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying mechanisms are not entirely known,53 it has been shown that residual host T cells with specific anti-donor or suppressive activity play a fundamental role, both in HLA matched and mismatched settings. Also, recipient natural killer (NK) cells are involved in the pathogenetic pathways leading to graft failure.…”
Section: Hemopoietic Stem Cell Homing and Engraftment Defectsmentioning
confidence: 99%